Modelling and Fuzzy Logic Control of an Underactuated Tower Crane System - Liyana Ramli; Izzuddin M. Lazim; Hazriq Izzuan Jaafar; Zaharuddin Mohamed (Applications of Modelling and Simulation (AMS), 2024)
Non-Indexed Publication